Langerhans Cell Histiocytosis of the Thyroid with Multiple Cervical Lymph Node Involvement Accompanying Metastatic Thyroid Papillary Carcinoma - A. Bahar Ceyran; Serkan Şenol; Barış Bayraktar; Şeyma Özkanlı; Z. Leyla Cinel; Abdullah Aydın (Case Reports in Pathology)
A 37-year-old male case was admitted with goiter. Ultrasonography of thyroid showed a 5 cm cystic nodule in the left lobe with a 1.5 cm solid component. Fine needle aspiration biopsy revealed atypia of undetermined significance or follicular lesion. The patient was operated on. The pathological diagnosis was reported as papillary thyroid carcinoma. The immunohistochemical examination showed multiple foci of Langerhans cell histiocytosis involving both lobes. The patient died due to cardiac arrest with respiratory causes in the early postoperative period. Langerhans cell histiocytosis is a rare primary condition which involves abnormal clonal proliferation of Langerhans cells in various tissues and organs. Thyroid involvement is infrequently seen. Although the etiology is unknown, genetic components may be linked to the disease. It is also associated with a family history of thyroid disease. Papillary thyroid carcinoma is the most common malignant epithelial tumor of the thyroid gland. Langerhans cell histiocytosis presenting with papillary thyroid carcinoma is rare. The privilege of our case is langerhans cell histiocytosis of the thyroid with multiple cervical lymph node involvement accompanying cervical lymph node metastatic thyroid papillary carcinoma.